Genetic Relationship Among Ten Promising Eggplant Varieties Using RAPD Markers - Biswas, Md. Sanaullah; Akhond, Md. Abdullah Yousuf; Al-Amin, Md.; Khatun, Mahmuda; Kabir, Muhammed Rezwan (Plant Tissue Culture and Biotechnology, 2010)
RAPD technique was used as a tool for assessing genetic diversity and varietal relationships among ten varieties of eggplant. Out of 21 primers screened four were selected. With these primers 76 clear and bright fragments were obtained of which 44 fragments considered polymorphic. The proportion of polymorphic loci and gene diversity values across all loci were 57.89% and 0.23, respectively. The UPGMA dendrogram based on genetic distance segregated the ten varieties of eggplant into two main clusters. Dohazari, Kazla, Nayantara and ISD-006 were grouped together in cluster I whereas Uttara, Islampuri, Khatkhatia, Singnath, BARI Begun-08 and Eggplant Line-083 into cluster II. Kazla and Nayantara variety pair was very close to each other with the highest intervarietal similarity index (92.54%) and lowest genetic distance (0.14). On the other hand, Khatkhatia and Nayantara pair was the lowest intervarietal similarity index (41.67%) with highest genetic distance (0.48). Therefore, identification of genetically distinct varieties using RAPD markers could be a potential tool for eggplant improvement. Key words: Eggplant, Polymorphism, Genetic relationship, RAPD D.O.I. 10.3329/ptcb.v19i2.5006 <span style="font-size: 9pt; font-family: Palatino; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-size: 12.0pt; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Plant Tissue Cult. & Biotech. 19(2): 119-126, 2009 (December)